Atypical skin manifestation of purpura fulminans in Chikungunya infection on elderly patients: A case report: Atypical skin manifestation in Chikungunya infection on elderly patients - Dankul, Parita; Ratanarat, Ranistha (Clinical Critical Care, 2024)
Background: Chikungunya is a vector-borne infectious disease that is usually characterized by fever, joint pain, muscle ache, headache, rash, or fatigue. Severe life-threatening complications such as septic shock, acute respiratory distress syndrome, and multiple organ dysfunction can develop during the acute phase of the disease. Purpura fulminans were rarely reported. Case presentation: A previously healthy 69-year-old male patient with no known medical history presented with a 3-day history of fever, malaise, and arthralgia at both knees. He developed dyspnea, purpura, and hemorrhagic blebs at the right leg for 1 day. He was initially diagnosed with sepsis and oliguric renal failure with severe lactic acidosis. After fluid therapy was given to maintain stable hemodynamics, his lactate level increased rapidly. Continuous renal replacement therapy and hemoperfusion with cytokine adsorbent were then initiated simultaneously. On the second day of admission, the skin and soft tissue lesions progressed rapidly, and the patient experienced refractory shock and multiple organ dysfunction. Finally, he was diagnosed with a Chikungunya infection. Three days following the onset of edema in his extremities, he expired. Conclusion: Purpuric skin manifestations and shock are rare but serious in Chikungunya infections. Clinicians should be aware of the potential for life-threatening complications. Aggressive management and adjunctive therapy such as hemoperfusion and intravenous immunoglobulins should be further studied.